Statistical Analysis of the Factors which can Influence the Results of Therapy by Root Amputation on Bridge Abutment Teeth - Constantin Daguci; Luminita Daguci; Mihaela Pauna; Norina Consuela Forna; Veronica Mercut; Mihail Raul Popescu; Oana-Cella Andrei; Ruxandra Margarit; Marilena Bataiosu (Romanian Society of Oral Rehabilitation, 2012)
In this study we have monitored the assessment of the prognosis related to the root amputation therapy and the examination of factors which influenced the failures and had an effect upon the viability of this surgical technique. The statistical analysis carried out within this study comprised two groups of patients summarizing a total number of 146 patients; the study was carried out for a period of 8 years, between 2003 and 2011 respectively. The overall number of patients examined was divided in two groups, maxillary and mandibular. The results of the study evidenced that the failure rate due to periodontal diseases for the two groups of patients represented 30.8%. A higher percentage was recorded for Group 1 - Maxillary as compared to Group 2 - Mandibular. The results of the coronary radicular amputation could be impacted by different factors, known as risk factors which affect the evolution of the periodontal disease; a significant role for that purpose is played by those factors related to the inner resection, to the patient, to the respective tooth and its topography.